Hate Crime Victimization and Weapon Use - Malcom, Zachary T. (Criminal justice and behavior, 2021)
Prior research has suggested that hate crimes hurt more, in that they are more physically severe than other crimes. A separate body of research has focused on the role of weapons in exacerbating violence; yet, no research has considered the role of weapon use in bias crime victimization. Following this, this research examines the relationship between weapon use, bias motivation, and victimization in the United States. On one hand, weapons may play an important role in hate crime by exacerbating violence. On the other hand, weapons may be unnecessary for facilitating hate crime violence, given the animus associated with bias motivation. Using data from the National Incident-Based Reporting System, we find that bias crimes are both (a) less likely than nonbias crimes to involve weapons and (b) more likely than nonbias crimes to involve serious or lethal victim injury. These patterns are particularly pronounced for antisexual orientation hate crimes.